Motus dei: the movement of God to disciple the nations - Farah, Warrick (William Carey Library, 2021)
An incredible breakthrough in missions history is taking place as disciples of Jesus make more disciples of Jesus around the globe, particularly among the least-reached. But what exactly are these church planting or disciple making movements? Where are they occurring and what are their unifying features? How are they manifesting in diverse populations? And can you or your organization be instrumental in catalyzing more movements? Motus Dei, Latin for "movement of God," seeks to answer these questions and more. Warrick Farah has expertly synthesized an extensive conversation between mission practitioners, scholars, and seasoned movement leaders from around the world. The resulting in-depth analysis of movements provides a multi-disciplinary academic investigation of an emerging "movements missiology," highlighting the importance of theology, social sciences, ethnology and anthropology, communications theory, leadership theory, and statistical analysis. Motus Dei locates the current Church Planting Movement (CPM) phenomenon within modern history, while tracing its roots back to the first century, and articulates a missiological description of the dynamics of Disciple Making Movements (DMMs) in Asia, Africa, and diaspora contexts in the Global North. Offering over thirty first-hand accounts of indigenous churches planting churches among the nations, Motus Dei provides a seedbed for growing movements in diverse contexts. There are lessons to be learned here by anyone seeking to participate in the movement of God. --